Evaluation of LG's anticancer acti•vi•ty on human gastric cancer cell line HGC-27 via molecular docking and gene expression analysis - Ciraci, Enver; Yurttas, Asiye Gok; Elgun, Tugba; Badilli, Beyza Nur; Kefeli, Melike; Keskin, Zeynep; Karagulle, Onur O. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2026)
Gastric cancer (GC) is one of the most prevalent gastrointestinal malignancies and continues to pose a significant global health burden. Repurposing clinically approved drugs is a cost-effective strategy for identifying new anticancer agents. In this study, the anticancer effects of linagliptin (LG), a dipeptidyl peptidase-4 (DPP-4) inhibitor, were evaluated in the human gastric cancer cell line HGC-27. LG significantly reduced cell viability in a dose-dependent manner, with a half-maximal inhibitory concentration (IC50) value of 50.29 mu M, and increased apoptotic cell death as confirmed by flow cytometry. Gene expression analysis revealed significant downregulation of Smoothened (SMO) and split hand and foot malformation 1 (SHFM1) and upregulation of Sonic hedgehog (SHH), indicating modulation of Hedgehog signaling. In addition, LG treatment resulted in reduced global DNA methylation levels. Molecular docking analyses demonstrated favorable binding affinities between LG and key Hedgehog pathway proteins, supporting a potential mechanistic basis for the observed biological effects. Collectively, these findings suggest that LG exhibits antiproliferative and pro-apoptotic activity in gastric cancer cells and may represent a promising candidate for drug repurposing in gastric cancer therapy.
Keywords: Gastric cancer; LG; Drug repurposing; Hedgehog signaling; Molecular docking; Apoptosis; Gene expression; HEDGEHOG PATHWAY; SONIC HEDGEHOG; PROGRESSION; CARCINOMAS; ACTIVATION; GROWTH; Biochemistry & Molecular Biology; Biophysics